Programme of Studies of the Specialty of Normal and Pathological Physiology. Achievements and Challenges in the Current Context - Adorna Carmenate, Zulema (Revista Cubana de Investigaciones Biomédicas, 2020)
Introduction: The programs of residences sometimes are extensives and there are deficiencies in the general strategy of teaching. Objective: identifying the susceptible of modification aspects in the effective Programme of Studies of the Specialty of Normal and Pathological Physiology, keeping in mind the current necessities, with a view to the future redraws of this Programme. Materials and methods: It was carried out a descriptive exploratory study. Three surveys were elaborated and applied about the Programme of Studies from the Specialty of Physiology to residents and specialists, to professors that have taught with this Programme of Studies and to professors that have worked with specialists graduated by this Programme of Studies. Results: In general, the results showed that the residence is extensive, there are deficiencies in the general strategy of teaching, it is necessary to review the pertinency and the programs of subjects and modules, as well as to elevate the quality of the education in the work and to carry out actions to perfect the resident's preparation to do the investigative and administrative functions. Conclusions: It would bear it to carry out modifications in the Programme of Studies of the Specialty of Normal and Pathological Physiology of the year 2000 as for: professional profile, organization strategies and development of the Programme of Studies, contents of the areas of knowledge, bibliography and evaluation system.